2023
DOI: 10.1038/s41598-023-30897-1
|View full text |Cite
|
Sign up to set email alerts
|

Sniffer dogs performance is stable over time in detecting COVID-19 positive samples and agrees with the rapid antigen test in the field

Abstract: Rapid antigen diagnostic (RAD) tests have been developed for the identification of the SARS-CoV-2 infection. However, they require nasopharyngeal or nasal swab, which is invasive, uncomfortable, and aerosolising. The use of saliva test was also proposed but has not yet been validated. Trained dogs may efficiently smell the presence of SARS-CoV-2 in biological samples of infected people, but further validation is needed both in laboratory and in field. The present study aimed to (1) assess and validate the stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Health care workers have reportedly used scent to triage illness, and in studies as early as 1960, when it was shown that sweat from schizophrenic and non-schizophrenic patients could be distinguished by trained rats using odour alone 17 . There is a growing body of evidence that disease-specific volatile organic compounds (VOCs) could be used for the early detection of disease before more obvious clinical signs or symptoms become apparent 18 . The mechanism for the release of volatiles is not well studied and varies with disease.…”
Section: Introductionmentioning
confidence: 99%
“…Health care workers have reportedly used scent to triage illness, and in studies as early as 1960, when it was shown that sweat from schizophrenic and non-schizophrenic patients could be distinguished by trained rats using odour alone 17 . There is a growing body of evidence that disease-specific volatile organic compounds (VOCs) could be used for the early detection of disease before more obvious clinical signs or symptoms become apparent 18 . The mechanism for the release of volatiles is not well studied and varies with disease.…”
Section: Introductionmentioning
confidence: 99%